(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
The mangrove biodiversity of Indonesia is rich and offers great potential for the discovery of bioactive compounds. The mangrove plant known as jeruju (Acanthus ilicifolius) has long been used in medicine and is recognized to include endophytic fungus capable of generating biologically active secondary metabolites. This investigation’s goal was to distinguish and assess endophytic fungi from the stem of A. ilicifolius as possible sources of antibacterial and antioxidant substances. After being isolated using surface sterilization techniques and cultivated on suitable media, endophytic fungi were characterized both macroscopically and microscopically. Liquid fermentation and solvent extraction were used to produce fungal extracts. Antioxidant activity was measured using the DPPH method, while antibacterial activity against many harmful bacteria was measured using the disc diffusion method. According to the results, the isolated endophytic fungus displayed a range of morphological characteristics and bioactivities. Among the isolates, BR6, which was identified as Penicillium sp., showed the greatest antioxidantsactivity with an IC50 value of 28.1 µg/mL. This isolate also shown strong antibacterial activity, has over 70% inhibition rates against Staphylococcussaureus, Bacillusssubtilis, Escherichiaccoli, and Salmonellattyphi. These findings imply that endophytic fungi from A. ilicifolius, particularly Penicillium sp., have significant potential as natural sources of antioxidant and antibacterial compounds for use in pharmaceutical and medical applications.